KENAIKAN PROSENTASE NAFKAH PEMELIHARAAN ANAK PASCA PERCERAIAN DALAM GUGATAN REKONPENSI - Nada Rahman, Aulia (Irtifaq, 2019)
The article discusses the increase in percentage ofmaintenance of post - divorce child in the case of recopension lawsuit.As is known despite the cost of living and maintenance of the child(hadhanah) has been described in the Quran and al-Hadith, but postdivorce does not result in the breakdown of the obligations of thefather-child subsidies. On the one hand it seems that there has been aninjustice to the post-divorce husband, but on the other hand the judgehas ex officio rights in checking, breaking and resolving divorcematters. Keywords: Maintenance, child maintenance (hadhanah), reconstruction